Docking Studies, Synthesis, Characterization and Evaluation of Their Antioxidant and Cytotoxic Activities of Some Novel Isoxazole-Substituted 9-Anilinoacridine Derivatives - R. Kalirajan; M. H. Mohammed Rafick; S. Sankar; S. Jubie (The Scientific World Journal)
A convenient synthesis of novel isoxazole-substituted 9-anilinoacridine derivatives 5a–j was reported. The compounds were confirmed by physical and analytical data and screened for in vitro antioxidant activity by DPPH method, reducing power assay and total antioxidant capacity method. The cytotoxic activity of the compounds was also studied in HEp-2 cell line. The docking studies of the synthesized compounds were performed towards the key nucleoside dsDNA by using AutoDock vina 4.0 programme. All the isoxazole-substituted compounds have significant activities.